PENERAPAN GREEN ACCOUNTING PADA UMKM DALAM MENDORONG INKLUSI HIJAU DAN KEADILAN LINGKUNGAN BERBASIS SDGs: A SYSTEMATIC LITERATURE REVIEW - Nining Sudiyarti; Rosyidah Rachman; Marisa Sutanty; Eko Sutrisno; Asmini Asmini (Penerbit Lafadz Jaya, 2026)
This study analyzes the relationship between green accounting and the achievement of the Sustainable Development Goals (SDGs) through a Systematic Literature Review (SLR) using the PRISMA 2020 guidelines. A total of 847 articles were identified from Scopus, Web of Science, and Google Scholar databases (2019–2024), of which 45 articles met the selection criteria for final analysis. The findings indicate that the implementation of green accounting significantly contributes to SDG 6 (Clean Water and Sanitation), SDG 7 (Affordable and Clean Energy), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 15 (Life on Land). Companies implementing green accounting demonstrate better sustainability performance (β = 0.42–0.72), a more positive reputation among investors, and greater contributions toward achieving the SDGs. This study integrates legitimacy theory, stakeholder theory, and institutional theory into a single conceptual framework to explain the underlying mechanisms of these relationships.